Corticosteroid-associated lupus pancreatitis: a case series and systematic review of the literature. (May 2019) - Dwivedi, P; Kumar, R R; Dhooria, A; Adarsh, M B; Malhotra, S; Kakkar, N; Naidu, S; Sharma, S K; Sharma, A; Jain, S; Dhir, V
Background: Acute pancreatitis is an uncommon complication that occurs in 0.85% to 4% of patients with systemic lupus erythematosus (SLE). In some patients, it occurs within days to weeks of starting medium-to-high dose corticosteroids. The authors have used the term 'corticosteroid-associated lupus pancreatitis' for these patients, and they report a case series and perform a systematic review of previously published reports. Methods: For the purpose of this study, corticosteroid-associated lupus pancreatitis was defined as occurrence of acute pancreatitis in patients with SLE (fulfilling the 1997 ACR), within 3 weeks of starting therapy with medium-to-high dose corticosteroids – either newly initiated or escalated from a lower dose. All patients with SLE admitted in the last 2.5 years in a North Indian university hospital were reviewed, and those with pancreatitis who fulfilled the above criteria were included in the case series. For the systematic review, a PUBMED search using the keywords 'lupus' and 'pancreatitis' was performed, and reports in English were reviewed for an association with corticosteroids. Results: Among 420 admissions of SLE patients, six patients (1.4%) fulfilled criteria for corticosteroid-associated lupus pancreatitis. All were female, with mean age and disease duration of 19.7 ± 3.3 and 3.8 ± 2.5 years respectively. All had active disease and developed acute pancreatitis within 48–72 hours of newly initiating medium-to-high dose corticosteroids (in three patients) or escalating them to medium–high dose (in three patients). After the development of pancreatitis, corticosteroids were continued in all except one patient. In addition, two patients received pulse methylprednisolone, two received pulse cyclophosphamide and one was started on azathioprine. Three patients died during hospitalization, all with severe pancreatitis. On systematic review, among 451 cases of lupus pancreatitis reported, 23 (5%) fulfilled criteria for 'corticosteroid-associated lupus pancreatitis'. A majority of them had pancreatitis within 3 days of starting treatment with medium-to-high dose corticosteroids. The mortality in these patients was 37.5%. Conclusion: In a small but substantial proportion of patients with lupus who develop pancreatitis, it occurs within days to weeks of starting medium-to-high dose corticosteroids. Many of these patients continue to receive corticosteroids, and some receive more aggressive immunosuppression. However, they have significant mortality, and further studies are required to identify appropriate treatment in this subgroup of patients.